Formation of Sn@C yolk-shell nanospheres and core-sheath nanowires for highly reversible lithium storage - Ni, Wei (2014)
As one promising anode material with high theoretical capacity, metallic tin has attracted much research interest in the field of lithium-ion batteries. Here, two types of tin/carbon (Sn@C) core–shell nanostructures with inner buffering voids are fabricated from SnO2 hollow nanospheres via a facile chemical vapor deposition (CVD) method. The crystallinity and surface topography of SnO2 hollow nanospheres are found to affect the morphology of resultant Sn@C materials. Sn@C yolk–shell nanospheres and core–sheath nanowires are obtained from the as-prepared SnO2 and high-temperature annealed SnO2 nanospheres, respectively. The unique Sn@C nanostructures can mitigate the agglomeration/pulverization of Sn nanoparticles and electrical disconnection from the current collector caused by the large volume change during the lithium alloying/dealloying process. Both Sn@C yolk–shell and core–sheath nanostructures show stable cycling performance up to 500 cycles with specific capacities of ca. 430 and 520 mA h g−1, respectively.